From nature to engineering: performance assessment of bioinspired flow fields in PEM fuel cells - Sevinc, Huseyin; Hazar, Hanbey (Elsevier Sci Ltd, 2026)
Proton exchange membrane fuel cells (PEMFCs) hold strong potential as clean energy conversion systems; however, their practical performance is often constrained by non-uniform reactant transport, local overheating, and parasitic pumping losses. This study addresses these challenges by proposing a set of bioinspired flow field designs for bipolar plates, derived from natural transport systems such as brain cells, lymphatic pathways, snowflakes, leaves, and galactic structures. A conventional triple-serpentine configuration was employed as the reference model. Three-dimensional CFD simulations were conducted to investigate temperature and pressure distributions, hydrogen and oxygen mass fraction profiles, reaction heat generation, and electrochemical behavior under identical boundary conditions. The results indicate that flow field geometry has a decisive influence on balancing heat and mass transport phenomena. The brain cell and snowflake models yielded the most uniform temperature distribution, while the lymphatic pathway minimized pumping losses by 38.6% compared to the serpentine baseline. Conversely, the leaf-and galaxy-inspired designs exhibited superior reactant distribution across the catalyst layer. At 0.4 V, the leaf configuration achieved the highest performance with a current density of 1.25 A cm-2 and a net power output of 12.45 W, outperforming the serpentine design by 4.61% and 4.36%, respectively. Although a single-phase model was adopted, its implications for water management were discussed to ensure physical consistency. Overall, the comparative results highlight the distinct advantages and limitations of each bioinspired architecture, providing practical insights for the geometric optimization of next-generation PEMFC bipolar plates.
Keywords: Bipolar Plate Design; Bioinspired Flow Fields; Net Power Output; Proton Exchange Membrane Fuel Cell (PEMFC)